Administrative Governance in State Institutions: A Comparative Study between Iraq and the GCC Countries - Fawzi Yousif , Lect. Dr. Emad (Basra studies journal, 2026)
The current study found out that the application of governance in Iraqi public administration continues to face numerous legal and institutional challenges, despite the existence of a revised legislative framework that enables improved performance of the administrative apparatus and establishes the foundations of transparency and accountability. A comparison with similar Gulf experiences demonstrates that the success of governance depends not only on the existence of legislation but also on its effective implementation at the organizational level, encompassing both management and oversight. It is evident that empowering institutions with greater autonomy, clarifying the division of powers, and strengthening both administrative and judicial oversight are essential prerequisites for addressing Iraqi administration according to modern governance standards. In light of these findings, there is an urgent need for parallel reform in both legislation and administration to ensure the practical and effective translation of governance principles into reality within state institutions.